Tc-99m NIDP and Tc-99m HMPAO labelled leukocyte scans in tuberculous spondylitis - Mohamad, Abdul R; Shuaib, Ibrahim L; Razak, Ruslan; Abdullah, Abdul H (1999)
A study was undertaken to assess the pattern of uptake on bone and labelled leukocyte scans in tuberculous spondylitis. Nine consecutive newly diagnosed cases were studied with Tc-99m MDP bone scans and Tc-99m HMPAO labelled leukocyte scans.The patients had basic laboratory investigations, plain chest and spine radiographs and computed tomography of the spine. Static images of bone scans were acquired at 3 hours and labelled leukocyte scans were acquired at 1,3 and 24 hours post-injection. A total of 11 spinal lesions were detected. Six bone scans were done demonstrating eight lesions and all showed abnormally increased activity.Labelled leukocyte scans were done in eight patients involving ten lesions and all except one showed photopaenic defects at the regions of interest.Both bone scan and leukocyte scan provided important information about the extent of the lesions and the combination of their pattern of uptake helped in the diagnosis of tuberculous spondylitis.